Leadership Training for Migrant Workers in Building A Resilient Generation and Competitive - Siwiyanti, Leonita; Ratnasari, Jujun (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service activity aims to provide interactive leadership training to the children of migrant workers and raise awareness of the importance of education and self-development. The programme aims to help children develop social and leadership skills that can be used in daily life. The methods include interactive discussions, focus groups, and participatory group work. The main activity is assembling a puzzle that is part of a group exercise, accompanied by delivering inspirational stories about great leaders to motivate participants to practise cooperation and decision-making in real-life situations. The training involved children of migrant workers aged 10-18 years in migrant communities in Malaysia. The evaluation instruments for this activity include participant satisfaction questionnaires and pre-post tests to measure knowledge and skill improvement. The collected data was analysed using descriptive statistical techniques, and a comparison of pre- and post-training test results was made to assess the effectiveness of the programme. The results of the activity showed a significant improvement in leadership understanding and confidence, as well as communication and teamwork skills. Participants were more enthusiastic and active in discussions and were able to apply the concept of leadership in daily life. Experience- and practice-based approaches have proven to be more effective than theoretical approaches, which allow participants to learn through real practice. This programme empowers children of migrant workers to be better prepared for challenges and to play an active role in their communities. In addition, this training model can be adapted for leadership development programmes in other marginalised communities.